Students’ perceptions of the effectiveness of their in-service training for the Advanced Certificate in Education programme - Ndlovu, MC (South African Journal of Higher Education, 2011)
The purpose of this study was to determine in-service students’ perceptions of the effectiveness of the Advanced Certificate in Education (ACE) programme offered by Stellenbosch University, South Africa, in preparing them to be confident teachers of Mathematical Literacy, Life Sciences or Physical Sciences in the Further Education and Training (FET) phase. An open-ended questionnaire was administered at the end of the first year of the two-year mixed-mode part-time study. The university’s standard student feedback questionnaire was administered during contact sessions. A Likert-type 5-point scale version of the initial open-ended questionnaire was designed and administered to the cohort after graduation. Findings were that there were process, content, contextual and outcomes aspects of the programme which were consistently positive and needed to be maintained. There were aspects that were initially perceived negatively or positively but sentiment changed after graduation. There were also aspects that were consistently perceived negatively and needed improvement.